Executive Committee Minutes 2017-08-24 - Academic Senate:::::::::
Agenda amended and approved. Minutes of 5/11/17 approve. Chair report. President Report. Provost Report. Graduation form – request to digitize. Digitizing Operations and Relations with International partners. Debrief of Commencement. SEIE Grievance policy referred to SAC. Senate Agenda approved. Periodic Review of Coaches.